(3OhQ GdeTQa GdJQHhj aj JMSjf HjFI GdJYdje hGdJYde HOhdI GdchjJ ai VhA eONd EOGQI GdJejR (B:s (3JUhQ ebJQM (B/s - (3fhQg eWQ HTjJ ZGdH GdQMjdi(B.s; (3eMehO MSGf SYjO(B.s (2022)
(3gOaJ GdOQGSI GdMGdjI Edi JYQa OhQ GdeTQa GdJQHhj aj JMSjf HjFI GdJYdje hGdJYde HOhdI GdchjJ ai VhA eONd EOGQI GdJejR, hGdJYQa Ydi adSaI EOGQI GdJejR heaghegG hNUGFUgG, hGdcTa Yf OhQ GdeTQa GdJQHhj aj JMSjf HjFI GdJYdje hGdJYde dJMbjb GdJejR aj eOGQS GdJYdje GdYGe HGdchjJ, hJMOjO hHdhQI Cge GdeYhbGJ hGdYbHGJ GdEOGQjI GdJj JMhd Ohf JMSjf HjFI GdJYdje hGdJYde dJMbjb GdJejR, hGdhbha Ydi feGPL GdETQGa GdJQHhj hLhGFR GdJejR GdYGdejI GdJj JSge aj JMSjf HjFI GdJYdje hGdJYde, hhVY edGeM GdJUhQ GdebJQM dJMSjf HjFI GdJYdje hGdJYde aj GdJYdje GdYGe HOhdI GdchjJ aj VhA eONd EOGQI GdJejR(B.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI, (B2022.s
(3HHdjhLQGajG(B: (3U(B. 142-155.s
Keywords: (3GdETQGa GdJQHhj(B--s; (3OhdI GdchjJ(B.s